Layered oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered oxide positive electrode material

The one-step synthesis of sodium ion battery layered oxide positive electrode material is solved, and the problems of high processing cost and elemental segregation of the sodium ion battery layered oxide positive electrode material are achieved, and lower cost and better battery performance are achieved.

CN119133408AActive Publication Date: 2024-12-13XIAN NAYI NEW ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411285048.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The high processing cost of layered oxide positive electrode materials of sodium ion batteries and elemental segregation problems lead to poor battery performance.

Method used

A single-step method is used to synthesize a layered oxide positive electrode material of sodium ion battery. By forming a metal or its salt and sodium salt in a solvent, a uniformly distributed positive electrode material is obtained by spraying pyrolysis and sintering, avoiding traditional precursors. Elemental segregation in the process.

Benefits of technology

The processing cost is reduced by about 40%, the discharge capacity and circulation performance of the positive electrode material are improved, the residual alkali content is reduced, and the uniformity of element distribution is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133408A_ABST
    Figure CN119133408A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery materials, and discloses a sodium ion battery layered oxide positive electrode material which is characterized in that the chemical formula is NaaNixFeyMnzM1-x-y-zO2, 0.8 < = a < = 1.1, 0 < = x < = 1, 0 < = y < = 1, 0 < = z < = 1, M = M1 + M2, M1 = at least one of Zn, Ca, Cu, Sb, Ba, Mg, Zr, Y, Cs, Mo, Sn, Ce, La, F, B, Ti, Zr and Li, and M2 = at least one of B, Al, Zr, Ti, Ce, W and P; and pyrolyzing and sintering the metal or the salt thereof in a solvent system to obtain a finished product. The low-cost process provided by the invention does not need to synthesize a precursor, but directly adopts a one-step method to synthesize the layered oxide positive electrode material of the sodium-ion battery. According to the method, the capacity, circulation and residual alkali of the sodium-ion battery are obviously improved, and large-scale popularization and application of the sodium-ion battery are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a sodium ion battery layered oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles, new energy batteries are also in constant research and development and innovation. From the perspective of classification, new energy batteries include lithium-ion batteries, sodium-ion batteries, lead-acid batteries, hydrogen fuel cells, etc. Among the above, lithium-ion batteries have gradually become the main part of modern new energy batteries due to their huge advantages in battery capacity, service life, safety performance, charging and discharging speed, and green environmental protection, but other new energy batteries still have certain market prospects.

[0003] Sodium-ion batteries mainly rely on the movement of sodium ions between the positive and negative electrodes to work. They work in a similar way to lithium-ion batteries, but they have the advantages of excellent low-temperature (-40°C) performance, high safety, zero-voltage transportation and storage, fast charging, and low cost. Therefore, the development of sodium-ion batteries is a favorable supplement and alternative to lithium iron phosphate lithium-ion batteries and ternary lithium-ion batteries. Due to the inherent advantages of sodium-ion batteries, they can be widely used in power tools, small energy storage, large energy storage, passenger cars and other fields. In the future, as the cost of sodium-ion batteries continues to decrease, it is an inevitable trend to replace lead-acid batteries used in two-wheeled vehicles and low-speed vehicles.

[0004] At present, the high cost of layered oxide positive electrode materials for sodium-ion batteries leads to high battery cell costs, which results in slow market promotion of sodium-ion batteries. However, one way to solve the high cost of layered oxide positive electrode materials is to reduce the processing cost of the materials, because the processing cost accounts for about 50% of the cost of the positive electrode materials. Usually, the preparation of layered oxide positive electrode materials is to first synthesize a hydroxide precursor, which is then mixed with a sodium source and sintered, and then post-processed to obtain the final product. The synthesis of hydroxide precursors not only has a long cycle, but also produces wastewater, waste gas, and waste residue. In addition, during the synthesis process of layered oxide precursors for sodium-ion batteries, due to Fe 2+The pH range for the precipitation of Fe(OH)2 in NaOH is 5.0-10.0, while the initial precipitation pH ranges of Ni(OH)2 and Mn(OH)2 are above 10.0, respectively. Therefore, in the synthesis process of nickel-iron-manganese layered oxide precursor, it is easy for iron ions to precipitate before nickel-manganese ions, resulting in the segregation of nickel-iron-manganese elements. Therefore, in the synthesis process of positive electrode materials, the segregation of nickel-iron-manganese transition metal elements usually causes the mixing of sodium elements and transition metal elements, thereby causing the sodium ion battery positive electrode material to have a higher residual alkali, lower capacity and poor cycle. Based on the above, reducing the processing cost of sodium ion battery layered oxide positive electrode materials and improving the segregation of elements is a key technical problem. Summary of the invention

[0005] Technical problems solved by the present invention:

[0006] It is used to solve the problems of high processing cost and element segregation of existing sodium ion battery layered oxide positive electrode materials.

[0007] The technical solution adopted by the present invention is:

[0008] In view of the above-mentioned technical problems, the object of the present invention is to provide a sodium ion battery layered oxide positive electrode material and a preparation method and application thereof.

[0009] In this scheme, a one-step method is used to synthesize the layered oxide positive electrode material for sodium ion batteries, that is, there is no need to synthesize a precursor, but a metal or its salt is prepared with a sodium salt to form a metal salt solution, and then pyrolyzed to obtain solid powder particles, and then sintered to obtain a positive electrode material with uniform element distribution. In the above, we further form a metal salt solution by adding nitric acid, ammonia water and a chelating agent. Spray pyrolysis is selected as the pyrolysis method, and after spray pyrolysis treatment, solid powder particles with uniform metal element distribution can be obtained. Although the sol-gel method can synthesize gel-like substances by adding a chelating agent and controlling pH, there are disadvantages such as complex control conditions, unstable batches, long synthesis cycle and difficulty in industrial production. As disclosed in the patent with publication number CN114520323A, in the process of heating the solvent to form a gel, it is easy to form upper and lower layers of the gel, which leads to uneven heating, so there will be an imbalance in the proportion of elements in the upper and lower layers of the gel and the phenomenon of uneven elements.

[0010] Based on this, the specific implementation plan is:

[0011] The present invention provides a sodium ion battery layered oxide positive electrode material, the chemical formula of which is Na a Ni x Fe y Mn z M 1-x-y- zO2; wherein, 0.8≤a≤1.1, 0≤x≤1, 0≤y≤1, 0≤z≤1, M=M1+M2, M1=at least one of Zn, Ca, Cu, Sb, Ba, Mg, Zr, Y, Cs, Mo, Sn, Ce, La, F, B, Ti, Zr, Li, M2=at least one of B, Al, Zr, Ti, Ce, W, P; the metal or its salt is thermally decomposed and sintered in a solvent system to obtain a finished product.

[0012] Further, the M1 source is introduced in the solvent system, and the M2 source is introduced during sintering.

[0013] In the present invention, the particle size D of the positive electrode material 50 =4~7μm.

[0014] In the present invention, the metal molar amount of the sodium source is A, the total metal molar amount of the nickel source, iron source, manganese source and M source is B, and A:B=0.8-1.1:1. Preferably, it can also be 0.8:1, 0.9:1, 1.0:1:, 1.1:1.

[0015] The present invention provides a method for preparing the aforementioned layered oxide positive electrode material for sodium ion batteries, comprising the following steps:

[0016] S1: placing a sodium source, a nickel source, an iron source, a manganese source and an M1 source in deionized water (solvent system), adding nitric acid, a chelating agent and aqueous ammonia, adjusting the pH of the solution to 5-7, and then spray pyrolysis to obtain an intermediate;

[0017] S2 sintered the intermediate once in a rotary kiln, and then coated with M2 source and sintered twice to obtain the positive electrode material.

[0018] In the above, the present invention obtains a solid powder with uniform distribution of elements such as sodium, nickel, iron and manganese by pyrolysis. Since the precursor and the sodium source mixture are not sintered in a sagger, they can be processed in a rotary kiln. The existing orbital kiln sintering is because a 3-15μm precursor and a 5-18 micron sodium source mixture are placed in a sagger for sintering, so this sintering method is more suitable; if the mixture is placed in a rotary kiln for sintering, the physical centrifugal effect will cause the precursor and the sodium source to separate, thereby causing segregation of sodium ions and elements such as nickel, iron and manganese, and ultimately leading to a decrease in the performance of the positive electrode material of the sodium ion battery.

[0019] In the present invention, the mass ratio of nitric acid, chelating agent and ammonia water is 0.1-1:0.015-0.5:1.5-2.5; the concentration of nitric acid is 2-5M.

[0020] In the present invention, the chelating agent is also called a complexing agent, which refers to a complex having a ligand action with a metal atom or ion and having a ring structure and containing two or more coordinating atoms. The chelating agent includes at least one of EDTA, DTPA, ATP, HEDP, EDTMPS, DTPMPA, citric acid, tartaric acid, oxalic acid, gluconic acid, polyacrylic acid, sodium gluconate and sodium citrate.

[0021] In the present invention, the sodium source is a sodium salt, and the sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.

[0022] In the present invention, the primary sintering is carried out at a temperature of 800 to 980°C and a time of 6 to 16 hours. Preferably, the temperature may be 800°C, 850°C, 880°C, 900°C, 950°C, 980°C and the aforementioned temperature ranges; similarly, the time may be 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours and the aforementioned time ranges.

[0023] In the present invention, the secondary sintering is carried out at a temperature of 400 to 800°C and a time of 5 to 10 hours. Preferably, the temperature may be 400°C, 500°C, 650°C, 700°C, 750°C, 800°C and the aforementioned temperature ranges; similarly, the time may be 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours and the aforementioned time ranges.

[0024] In the present invention, in the primary sintering and / or the secondary sintering, the sintering atmosphere is air, oxygen or a mixed gas with an oxygen concentration of more than 10%.

[0025] In the present invention, the nickel source, iron source, manganese source and M1 source are each independently selected from at least one of oxalate, acetate, nitrate, sulfate, chloride, oxide, hydroxide or metal powder.

[0026] In the present invention, the M1 source includes the following features:

[0027] The M1 source includes at least one of zinc oxide, zinc hydroxide, calcium oxide, calcium hydroxide, copper oxide, tellurium oxide, barium oxide, barium hydroxide, magnesium oxide, magnesium hydroxide, zirconium oxide, zirconium hydroxide, yttrium oxide, cesium oxide, molybdenum oxide, ammonium molybdate, tin oxide, cerium oxide, lanthanum oxide, ammonium fluoride, sodium fluoride, boron oxide, boric acid, titanium oxide, zirconium oxide, zirconium hydroxide, lithium hydroxide, and lithium carbonate;

[0028] In the present invention, the M2 source includes the following features:

[0029] The M2 source includes at least one of boron oxide, boric acid, aluminum oxide, aluminum hydroxide, zirconium oxide, zirconium hydroxide, titanium oxide, cerium oxide, ammonium tungstate, monoammonium phosphate, and diammonium phosphate;

[0030] The total mass ratio of M2 elements in the coating agent is 0.1-0.8%;

[0031] Particle size of coating agent D 50 <50nm.

[0032] The technical mechanism and beneficial effects adopted by the present invention are as follows:

[0033] (1) The present invention does not use the traditional precursor process method, but uses a one-step method to synthesize the sodium ion battery layered oxide positive electrode material, and its processing cost is reduced by more than 40% compared with the traditional process. For example, sodium source, nickel source, iron source, manganese source, nitric acid, ammonia water, chelating agent and dopant (M1 source) are added in the solution synthesis, and evenly distributed sodium, nickel, iron, manganese elements and doping elements are obtained by spray pyrolysis, and low-energy consumption rotary kiln sintering is used, which is conducive to reducing the residual alkali of the positive electrode material, increasing the discharge capacity and improving the cycle performance.

[0034] (2) The present invention adds nitric acid, a chelating agent and ammonia water, and utilizes nickel-iron-manganese metal powder or salts to react with nitric acid to form a nitrate solution, and the chelating agent can produce a chelating effect with the metal ions in the nitrate. Since ammonia water has a poor chelating effect on iron ions, it will cause the problem of uneven nickel-iron-manganese elements. Based on this, by adding other chelating agents with better chelating effects on iron ions, the purpose is to enhance the effect of uniform distribution of elements. Furthermore, by optimizing the amount of chelating agent, pH value, temperature and other parameters in the solution, the metal elements in the powder particles after spray pyrolysis can be kept uniformly distributed, and then a low-cost sodium ion battery layered oxide positive electrode material with uniform element distribution is obtained by rotary kiln sintering and back-end processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the EDS image of the layered oxide positive electrode material for sodium ion battery with low cost process in Example 1;

[0036] Figure 2 This is the EDS image of the layered oxide positive electrode material of the sodium ion battery using the conventional process in Comparative Example 1;

[0037] Figure 3 The capacity curve of the sodium ion battery layered oxide positive electrode material of Example 1 and Comparative Example 1;

[0038] Figure 4 The cycle curves of the layered oxide positive electrode materials for sodium ion batteries of Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0040] Example 1

[0041] This embodiment provides a method for preparing a layered oxide positive electrode material for a sodium ion battery with a low-cost process, comprising the following steps:

[0042] (1) According to the molecular formula Na 0.8-1.1 Ni 0.225 Fe 0.315 Mn 0.36 Cu 0.055 Zn 0.02 Ca 0.015 B 0.005 Li 0.005 O2, adding Na2CO3 and Ni, Fe, Mn and Cu metal powders and ZnO, CaO, B2O3, Li2CO3 dopants into deionized water, then adding 1% nitric acid with a concentration of 5M (calculated based on the total mass of the solvent), 2.5% ammonia water with a mass fraction (calculated based on the total mass of the solvent) and 0.50% (calculated based on the total mass of the solvent) of five chelating agents (EDTA, DTPA, ATP, HEDP and sodium gluconate, the ratio of the foregoing components is 1:1:1:1:1), adjusting the pH of the solution to 7, and then obtaining a solid powder substance by spray pyrolysis;

[0043] (2) The solid powder material is sintered and kept in air atmosphere in a rotary kiln at 880°C for 16 hours, crushed and sieved, and then coated with three coating agents of Al2O3, ZrO2 and TiO2 with a mass ratio of 0.5% (Al+Zr+Ti) in a coating machine, and the size of the three coating agents is less than 50nm. Then, it is sintered and kept in air atmosphere in a rotary kiln at 600°C for 8 hours, crushed and sieved, and finally a 4μm sodium ion battery layered oxide positive electrode material is obtained.

[0044] Example 2

[0045] This embodiment provides a method for preparing a layered oxide positive electrode material for a sodium ion battery with a low-cost process, comprising the following steps:

[0046] (1) According to the molecular formula Na 0.8-1.1 Fe 0.40 Mn 0.40 Zn 0.01 Ca 0.015 Mo 0.005 O 0.19 F0.01 , NaOH, FeO, MnO, ZnO, CaO, MoO2, and NH4F are added to deionized water, and then 4.5M nitric acid (calculated based on the total mass of the solvent) with a concentration of 0.1%, ammonia water with a mass fraction of 1.5%, and five chelating agents (EDTMPS, DTPMPA, citric acid, tartaric acid, and oxalic acid, with a ratio of 1:1:1:1:1) with a mass fraction of 0.015% (calculated based on the total mass of the solvent) are added, the pH of the solution is adjusted to 5, and then a solid powder material is obtained by spray pyrolysis;

[0047] (2) The solid powder material is sintered and kept warm for 6 hours in a mixed atmosphere with an oxygen content of 10% in a rotary kiln at 980°C, crushed and sieved, and then coated with four coating agents of ZrO2, TiO2, CeO2 and WO3 with a mass ratio of 0.8% (Zr+Ti+Ce+W) in a coating machine, and the size of the four coating agents is less than 50nm. Then, it is sintered and kept warm for 5 hours in a rotary kiln at 800°C, and finally a 7μm sodium ion battery layered oxide positive electrode material is obtained after crushing and sieving.

[0048] Example 3

[0049] This embodiment provides a method for preparing a sodium ion battery layered oxide positive electrode material with a low-cost process, comprising the following steps:

[0050] (1) According to the molecular formula Na 0.8-1.1 Ni 0.36 Fe 0.18 Mn 0.36 Sb 0.010 Mg 0.005 Zr 0.06 Y 0.005 Cs 0.02 O2, adding NaHCO3 and Ni(OH)2, Fe(OH)2, Mn(OH)2, SbO, MgO, ZrO, Y2O3 and CsO2 into deionized water, then adding 3M nitric acid (calculated based on the total mass of the solvent), 2% ammonia water (calculated based on the total mass of the solvent) and 0.20% (calculated based on the total mass of the solvent) of four chelating agents (gluconic acid, polyacrylic acid, sodium gluconate and sodium citrate, the ratio of the above components is 1:1:1:1), adjusting the pH of the solution to 5.5, and then obtaining a solid powder substance by spray pyrolysis;

[0051] (2) The solid powder material is sintered and kept warm for 10 hours in a mixed atmosphere with an oxygen content of 10% in a rotary kiln at 940°C, crushed and sieved, and then coated with four coating agents of ZrO2, TiO2, CeO2 and NH4H2PO4 with a mass ratio of 0.1% (Zr+Ti+Ce+P) in a coating machine, and the size of the four coating agents is less than 50nm. Then, it is sintered and kept warm for 10 hours in a rotary kiln at 400°C for a second time, and after crushing and sieving, a 6μm sodium ion battery layered oxide positive electrode material is finally obtained.

[0052] Example 4

[0053] This embodiment provides a method for preparing a sodium ion battery layered oxide positive electrode material with a low-cost process, comprising the following steps:

[0054] (1) According to the molecular formula Na 0.8-1.1 Fe 0.70 Mn 0.26Mg0.005 Zr 0.005 Sn 0.005 Ti 0.005 O 0.19 F 0.01 O2, adding a mixture of NaHCO3H and NaHCO3, Fe(OH)2, Mn(OH)2, ZrO2, SnO, TiO2 and NH4F into deionized water, then adding 0.8% nitric acid with a concentration of 2M (calculated based on the total mass of the solvent), 2.5% ammonia water (calculated based on the total mass of the solvent) and 0.40% (calculated based on the total mass of the solvent) of two chelating agents (gluconic acid and citric acid, the ratio of the above components is 1:1), adjusting the pH of the solution to 5.6, and then obtaining a solid powder substance by spray pyrolysis;

[0055] (2) The solid powder material was sintered and kept warm for 10 hours in a mixed atmosphere with an oxygen content of 20% in a rotary kiln at 900°C, crushed and sieved, and then coated with 0.4% (Al+Zr+Ti+W) by mass of AlO in a coating machine. 3、 ZrO2, TiO2 and (NH4)6W7O 24 ·6H2O four coating agents, the size of the four coating agents are all less than 50nm. Then they are sintered for a second time in a rotary kiln at 650℃ for 5h, and finally pulverized and sieved to obtain a 5μm sodium ion battery layered oxide positive electrode material.

[0056] Example 5

[0057] This embodiment provides a method for preparing a layered oxide positive electrode material for a sodium ion battery with a low-cost process, comprising the following steps:

[0058] (1) According to the molecular formula Na 0.8-1.1 Ni 0.20Fe 0.35 Mn 0.35 Cu 0.055 Zn 0.02 Ca 0.015 La 0.005 Ti 0.005 O2, adding a NaHCO3 mixture with NiO, FeO, MnO, CuO, ZnO, CaO, La2O3 and TiO2 into deionized water, then adding 4M nitric acid (calculated based on the total mass of the solvent), 1.8% ammonia water (calculated based on the total mass of the solvent) and 0.25% (calculated based on the total mass of the solvent) of three chelating agents (DTMPS, DTPMPA and citric acid, the ratio of the aforementioned components is 1:1:1), adjusting the pH of the solution to 5.6, and then obtaining a solid powder substance by spray pyrolysis;

[0059] (2) The solid powder material is sintered and kept warm in an air atmosphere in a 920°C orbital kiln for 12 hours, crushed and sieved, and then coated with a B2O3 coating agent with a mass ratio of 0.6% B in a coating machine, and the size of B2O3 is less than 50nm. Then, it is sintered and kept warm for 6 hours in a rotary kiln at 550°C, and finally a 5μm sodium ion battery layered oxide positive electrode material is obtained after crushing and sieving.

[0060] Example 6

[0061] This embodiment provides a method for preparing a sodium ion battery layered oxide positive electrode material with a low-cost process, comprising the following steps:

[0062] (1) According to the molecular formula Na 0.8-1.1 Ni 0.25 Fe 0.35 Mn 0.30 Cu 0.050 Zn 0.025 Ca 0.015 B 0.005 Ce 0.005 O2, adding a mixture of Na2CO3 and NaOH and NiO, FeO, MnO, CuO, ZnO, CaO, B2O3 and CeO2 into deionized water, and then adding 0.7% nitric acid with a concentration of 2M (calculated based on the total mass of the solvent), 2.2% ammonia water (calculated based on the total mass of the solvent) and 0.12% (calculated based on the total mass of the solvent) of four chelating agents (DTPA, ATP, sodium gluconate and sodium citrate, the ratio of the above components is 1:1:1:1), adjusting the pH of the solution to 5.9, and then obtaining a solid powder substance by spray pyrolysis;

[0063] (2) The solid powder material is sintered and kept in an oxygen atmosphere in a 940°C orbital kiln for 16 hours, crushed and sieved, and then coated with four coating agents of ZrO2, TiO2, CeO2 and WO3 with a mass ratio of 0.4% (Zr+Ti+Ce+W) in a coating machine, and the size of the four coating agents is less than 50nm. Then, it is sintered and kept in a rotary kiln at 700°C for 5 hours, and finally a 6μm sodium ion battery layered oxide positive electrode material is obtained after crushing and sieving.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 1 is that a precursor process (sintering) is used to synthesize the sodium positive electrode material. The following is the precursor process synthesis process.

[0066] According to the molecular formula Na 0.8-1.1 Ni 0.225 Fe 0.315 Mn 0.36 Cu 0.055 Zn 0.02 Ca 0.015 B 0.005 Li 0.005 O2, Na2CO3 and NiFeMnCu hydroxide precursors and ZnO, CaO, B2O3, Li2CO3 were mixed, sintered and kept warm for 16 hours in an air atmosphere in an 880℃ orbital kiln, crushed and sieved, and then coated with 0.4% (Zr+Ti+Ce+W) mass ratio of ZrO2, TiO2, CeO2 and WO3 in a coating machine, and the size of the four coating agents was less than 50nm. Then, it was sintered and kept warm for 8 hours in a 600℃ rotary kiln, and finally a 4μm sodium ion battery layered oxide positive electrode material was obtained after crushing and sieving.

[0067] Comparative Example 2

[0068] The difference between this comparative example and Example 1 is that no chelating agent is added.

[0069] Test example

[0070] The aforementioned embodiments and comparative examples were used as samples to conduct performance tests on sodium ion layered oxide positive electrode material products.

[0071] 1. Free sodium or residual alkali test

[0072] The free sodium or residual alkali test uses an automatic potentiometric titrator, model: METTLER TOLEDO G20, to weigh 5g of sample solvent into 40mL of aqueous solution, ultrasonicate for 30min, filter, dilute to 100mL volumetric flask, shake well, let stand, and take the clear solution for testing. The results are shown in Table 1.

[0073] 2. Discharge capacity and cycle performance

[0074] The discharge capacity and cycle performance were tested by the following method: the sodium positive electrode material was mixed with conductive carbon black and binder PVDF in a mass ratio of 80:10:10, and NMP was added to make a uniform slurry and coated on aluminum foil. After drying and rolling, it was cut into positive electrode sheets with a diameter of 14 mm. CR2032 button cells were used to assemble sodium ion batteries. The separator was glass fiber, the electrolyte was a 1 mol / L NaPF6 solution with EC / PC / DEC as the solvent, and the negative electrode was a sodium sheet. The results are shown in Table 1 and Figure 1-2 As shown (the materials obtained in Example 1 and Comparative Example 1 were used as samples for measurement).

[0075] 3. Sodium ion battery testing

[0076] Sodium ion battery test conditions: temperature 25℃±1℃, charge and discharge cycle voltage range 2.0V-4.0V, current 0.1C (150mAh / g), cycle test was carried out at 0.5C charge and 1C discharge. The results are shown in Table 3.

[0077] Test results:

[0078] Figure 1 and Figure 2 The EDS graphs of Ni, Fe and Mn elements in the cross section of the positive electrode material of the sodium ion battery in Example 1 and Comparative Example 1 are shown respectively. Table 1 (spectra 24-30) and Table 2 (spectra 31-37) respectively give the molar ratios of Ni, Fe and Mn in the cross section of the sodium battery positive material in Example 1 and Comparative Example 1.

[0079] Table 1 Ni, Fe and Mn molar ratio in Example 1

[0080] Molar ratio Design Specifications 24 25 26 27 28 29 30 Ni / mol% 22.50±1.50 22.32 23.37 23.52 21.49 22.91 21.83 22.37 Fe / mol% 31.50±1.50 30.79 31.72 30.93 32.04 32.06 31.63 32.14 Mn / mol% 36.00±1.50 36.89 34.91 35.55 36.47 35.03 36.54 35.49

[0081] Table 2 Ni, Fe and Mn molar ratio in comparative example 1

[0082] Molar ratio Design Specifications 31 32 33 34 35 36 37 Ni / mol% 22.50±1.50 23.18 21.72 22.31 21.82 20.93 22.73 20.71 Fe / mol% 31.50±1.50 33.28 34.04 32.63 30.81 34.11 32.34 33.46 Mn / mol% 36.00±1.50 33.54 34.24 35.06 37.37 34.96 34.93 35.83

[0083] According to the EDS spectrum data in Table 1 and Table 2, the three elements of Ni, Fe, and Mn in Example 1 are all within the design specifications, indicating that the elements are evenly distributed and there is no segregation of the elements; while the three elements of Ni, Fe, and Mn in Comparative Example 1 are unevenly distributed, such as the molar amounts of Fe, Mn in Spectrum 31 and Fe, Mn in Spectrum 32 exceed the design specifications. This shows that the sodium positive material synthesized by the traditional precursor process is prone to uneven Ni, Fe, and Mn elements, and the reason is the uneven Ni, Fe, and Mn elements produced in the precursor synthesis. Since a chelating agent that can chelate with Ni, Fe, and Mn is added during the solution configuration process in the present invention, such as ethylenediaminetetraacetic acid (EDTA), which can effectively chelate with Ni, Fe, and Mn, it is not easy to produce uneven elements during the spray pyrolysis process.

[0084] In addition, the capacity and cycle comparison tests of the sodium ion battery positive electrode materials of Example 1 and Comparative Example 1 were performed respectively, and the data results were made into Figure 3 and Figure 4 , and Table 3 summarizes the comparative data of capacity, circulation, free sodium and pH of the embodiments and comparative examples.

[0085] Table 3 Physical and chemical test results

[0086]

[0087] As shown in Table 3, the sodium positive electrode materials prepared in Examples 1-6 have excellent discharge capacity, cycle, free sodium and pH value. For example, the 50-cycle cycle retention rate is above 94%, and the free sodium and pH value are below 0.9% and 12, respectively.

[0088] According to Table 3, the positive electrode material in Example 1: Na 0.8-1.1 Ni 0.225 Fe 0.315 Mn 0.36 Cu 0.055 Zn 0.02 Ca 0.015 B 0.005 Li 0.005The 0.1C first discharge capacity of O2 is 147mAh / g, the cycle retention rate of 50 weeks is 96.07%, the residual alkali and pH are 0.367% and 11.76 respectively; while the 0.1C first capacity in Comparative Example 1 is only 138mAh / g, the cycle retention rate of 50 weeks is 92.78%, the residual alkali and pH are 4.742% and 12.43 respectively. The above comparative data show that the uniform distribution of the three elements Ni, Fe, and Mn has obvious improvements on the capacity and cycle of sodium-ion positive materials. Since the three elements Ni, Fe, and Mn are usually in the metal layer of sodium-ion positive materials, if segregation occurs, the metal elements and sodium elements will be mixed, resulting in an increase in the resistance to the insertion and extraction of sodium ions, thereby causing the capacity and cycle performance of the sodium-ion battery positive material to decrease.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A layered oxide positive electrode material for a sodium ion battery, It is characterized in that The chemical formula is Na a Ni x Fe y Mn z M 1-x-y-z O 2 , 0.8≤a≤1.1, 0≤x≤1, 0≤y≤1, 0≤z≤1, M=M1+M2, M1=at least one of Zn, Ca, Cu, Sb, Ba, Mg, Zr, Y, Cs, Mo, Sn, Ce, La, F, B, Ti, Zr, Li, M2=at least one of B, Al, Zr, Ti, Ce, W, P; the metal or its salt is pyrolyzed and sintered in a solvent system.

2. The sodium ion battery layered oxide positive electrode material according to claim 1, It is characterized in that The M1 source is introduced in the solvent system, and the M2 source is introduced during sintering.

3. The sodium ion battery layered oxide positive electrode material according to claim 1, It is characterized in that The metal molar amount of the sodium source is A, the total metal molar amount of the nickel source, the iron source, the manganese source and the M source is B, and A:B=0.8-1.1:

1.

4. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to any one of claims 1 to 3, It is characterized in that The steps include: S1: placing sodium source, nickel source, iron source, manganese source and M1 source in deionized water, adding nitric acid, chelating agent and ammonia water, adjusting the pH of the solution to 5-7, and spray pyrolysis to obtain an intermediate; S2 sintered the intermediate once in a rotary kiln, and then coated with M2 source and sintered twice to obtain the positive electrode material.

5. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 4, It is characterized in that S1 includes at least one of features (S1-1) to (S1-2): (S1-1) the sodium source is a sodium salt, and the sodium salt includes at least one of sodium carbonate, sodium bicarbonate, and sodium hydroxide; (S1-2) The nickel source, iron source, manganese source and M1 source are each independently selected from at least one of oxalate, acetate, nitrate, sulfate, chloride, oxide, hydroxide or metal powder.

6. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 4, It is characterized in that S1 includes features (S1-3): (S1-3) The chelating agent includes at least one of EDTA, DTPA, ATP, HEDP, EDTMPS, DTPMPA, citric acid, tartaric acid, oxalic acid, gluconic acid, polyacrylic acid, sodium gluconate and sodium citrate.

7. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 4, It is characterized in that S1 includes at least one of features (S1-4) and (S1-5): (S1-4) the mass ratio of nitric acid, chelating agent and ammonia water is 0.1-1:0.015-0.5:1.5-2.5; (S1-5) The concentration of nitric acid is 2 to 5M.

8. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 4, It is characterized in that S2 includes at least one of features (S2-1) to (S2-3): (S2-1) primary sintering: temperature 800-980°C, time 6-16h; (S2-2) Secondary sintering: temperature 400-800°C, time 5-10h; (S2-3) During the primary sintering and / or the secondary sintering, the sintering atmosphere is air, oxygen or a mixed gas with an oxygen concentration of more than 10%.

9. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to any one of claims 4 to 8, It is characterized in that The M2 source includes at least one of the characteristics (1-1) to (1-3): (1-1) The M2 source includes at least one of boron oxide, boric acid, aluminum oxide, aluminum hydroxide, zirconium oxide, zirconium hydroxide, titanium oxide, cerium oxide, ammonium tungstate, monoammonium phosphate, and diammonium phosphate; (1-2) The total element mass ratio in the M2 source is 0.1-0.8%; (1-3) Granularity D of M2 source 50 <50nm.

10. The sodium ion battery layered oxide positive electrode material according to any one of claims 1 to 3, or the sodium ion battery layered oxide positive electrode material obtained by the preparation method according to any one of claims 4 to 9 is used in a sodium ion battery; the particle size D of the positive electrode material 50 =4~7μm.

Citation Information

Patent Citations

  • Sodium ion battery positive electrode material, and preparation method and application method thereof

    CN105692721A

  • Preparation method of high-capacity lithium-rich ternary positive electrode material

    CN108063226A

  • Electrode material for lithium-ion batteries prepared by rotary device and preparation method and application thereof

    CN110459759A

  • Layered oxide material and preparation method thereof, positive electrode material, positive electrode plate and lithium ion battery

    CN115974177A

  • Layered ternary positive electrode material of sodium-ion battery as well as preparation method and application of layered ternary positive electrode material

    CN117374248A

Cited By

  • Positive electrode active material and preparation method thereof, positive electrode slurry, positive electrode plate, sodium ion battery and application

    CN119852386A